Treatment Strategies: A Systematic Review of The Advancements of Topical Antibiotics for Impetigo - Aprillia, Ghea; Wicaksono, Ilham Setya (CV. Publikasi Indonesia, 2025)
Impetigo is a highly contagious bacterial skin infection affecting primarily children aged 2–5 years but also other age groups. It is predominantly caused by Staphylococcus aureus and Streptococcus pyogenes, with occasional involvement of anaerobic bacteria. Nonbullous impetigo accounts for 70% of cases and presents with characteristic golden-yellow crusting, while bullous impetigo manifests with toxin-induced fragile bullae. Effective management is crucial to address discomfort, cosmetic issues, and prevent complications. Topical antibiotics are first-line treatments for localized infections, while systemic antibiotics are reserved for severe or widespread cases. The increasing prevalence of antibiotic resistance, especially to mupirocin and fusidic acid, highlights the importance of adopting evidence-based treatment for effective strategies. Methods: This systematic review adheres to PRISMA 2020 guidelines. Eligible studies from 2014 to 2024 were identified through databases including PubMed, Embase, and Cochrane Library using terms related to impetigo treatment and antibiotic resistance. Studies evaluating the efficacy, safety, and resistance trends of antibiotics and alternative therapies were included. Data were extracted on demographics, interventions, outcomes, and adverse effects. Results: Emerging treatments, such as ozenoxacin, have shown promising results, offering superior efficacy and safety profiles compared to traditional agents like mupirocin and fusidic acid. Ozenoxacin demonstrated faster bacterial clearance and clinical resolution with minimal resistance development. Resistance to mupirocin and fusidic acid is increasingly concerning, highlighting the need for alternative therapies. Systemic antibiotics, including cephalexin and dicloxacillin, remain crucial for severe cases, but their use requires careful monitoring to mitigate adverse effects. Discussion: Antibiotic resistance poses a significant challenge in impetigo management. Topical therapies like ozenoxacin represent effective first-line options for localized infections, while systemic antibiotics address severe cases. Public health strategies emphasizing antibiotic stewardship, hygiene education, and accessible healthcare are essential to reduce the global burden of impetigo. Research on head-to-head comparisons of newer and traditional therapies will further refine treatment guidelines. Conclusion: Advances in impetigo management, particularly the introduction of ozenoxacin, offer effective solutions for localized infections. However, antibiotic resistance trends necessitate ongoing surveillance and research to optimize treatment strategies and improve patient outcomes globally.